The uniqueness of flipped learning approach - Abd Rahman, Siti Fatimah; Md Yunus, Melor; Hashim, Harwati (Conscientia Beam, 2020)
Pedagogical changes and adaptation of new models in teaching and learning should be considered as a means to develop a nation. One of the most popular growing models is flipped learning. Flipped learning is widely used all over the world in the teaching of different fields and subjects. It promotes meaningful learning, more student-centered rather than teacher-centered and is commonly aided with technological equipment such as pre-recorded videos, mobile apps or simply watching videos on YouTube before coming to the class. This paper reviews the level of participants, methodological approaches and the discipline of flipped learning research based on nineteen selected articles published in 2015 until 2019. The inductive content analysis examined the participants’ level, the methodological approaches used in conducting their research as well as the field of the research. Data was analyzed using descriptive analysis. The findings suggested that flipped learning is a great approach to be applied in the classroom regardless of the field of the study. It also could be an effective teaching method in the 21st century of education